Key drivers of migration due to violence in urban areas: a case of Medellin, Colombia - Melina Ocampo-González; Juan Gabino González-Becerril (Universidad Autónoma del Estado de México, 2018)
The displaced people of Colombia constitute one of the world´s largest populations of IDPs (IDMC 2017). This forced displacement is mainly caused by the internal conflict in the country, whose effects has expanded to some urban centres such as Medellin. Since then, intra-urban forced displacement has been a matter of great concern in this metropolitan area. The main aim of this research is to better understand violence-induced migration in urban areas, specifically in Medellin, Colombia, seeking to identify the challenges that any approach focused on preventing forced displacement in Medellin should take into consideration. For this purpose The Migration out of Povertys Drivers of Migration theory (2012) will be applied to this case study. The main sources of information will be the testimonies of Medellins forced displaced population from 2010 and observation during fieldwork carried out in the same year.